Impacts of temperatures and phosphoric-acid modification to the physicochemical properties of biochar for excellent sulfadiazine adsorption - Zeng, Xue-Yu; Wang, Yu; Li, Rong-Xin; Cao, Hai-Lei; Li, Ya-Feng; Lü, Jian (Biochar (Online), 2022)
The textural properties and surface chemistry of phosphoric acid-modified biochars (PABCs) prepared at different pyrolysis temperatures (500–700 °C) were studied based on the results obtained from XRD, SEM, BET, FT-IR, Raman, XPS and elements analyses. PABCs prepared at higher temperatures tended to possess a bigger proportion of microporous structure. The adsorption capacity and initial rate of PABCs for sulfadiazine (SDZ) were notably improved to 139.2 mg/g and 9.66 mg/(g min) as calculated from the Langmuir model. The adsorption equilibrium time was only one quarter of that without modification. The H 3 PO 4 modification was advantageous to produce phosphate and break functional groups to form disordered carbon structure abundant of micropores. The enhancement in the adsorption of SDZ was due to the confinement effect of hydrophobic cavities from the mircoporous structure and the π–π electron–donor–acceptor interaction. Specially, PABCs exhibited stable adsorption capacities at a wide pH range (3.0–9.0) or relatively high concentrations of coexisting ions. Highlights Phosphoric acid breaks functional groups to form disordered carbon and surface phosphate; The q m of PABCs for sulfadiazine reached 139.2 mg/g that was competitive to MWCNTs; The hydrophobicity of PABCs and π–π EDA interaction played a leading role for binding SDZ